Report of the Working Group on Cement Industry X Five Year Plan - 2002-07 - Planning Commission (Planning Commission, 2002)
The Planning Commission has constituted a Working Group on Cement Industry for formulation of X Five Year Plan (2002-2007) with the following terms of reference and composition.
Government of India Planning Commission
Government of India Planning Commission